2004
DOI: 10.1161/01.res.0000146030.53089.18
|View full text |Cite
|
Sign up to set email alerts
|

Role for Sterol Regulatory Element-Binding Protein in Activation of Endothelial Cells by Phospholipid Oxidation Products

Abstract: Abstract-Oxidized phospholipids, including oxidation products of palmitoyl-arachidonyl-phosphatidyl choline (PAPC), are mediators of inflammation in endothelial cells (ECs) and known to induce several chemokines, including interleukin-8 (IL-8). In this study, we show that oxidized PAPC (OxPAPC), which accumulates in atherosclerotic lesions, paradoxically depletes endothelial cholesterol, causing caveolin-1 internalization from the plasma membrane to the endoplasmic reticulum and Golgi, and activates sterol reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 50 publications
5
89
0
1
Order By: Relevance
“…Consistent with in vitro studies indicating that oxPAPC induces cytokine production through a sterolregulatory element binding protein (SREBP)-mediated mechanism (39,40), renal SREBP-1c mRNA levels increased dramatically in mice fed the Western diet, compared with the same mice on a chow diet (22). The increased SREBP-1c mRNA levels were associated with a significant increase in renal triglyceride levels.…”
supporting
confidence: 78%
“…Consistent with in vitro studies indicating that oxPAPC induces cytokine production through a sterolregulatory element binding protein (SREBP)-mediated mechanism (39,40), renal SREBP-1c mRNA levels increased dramatically in mice fed the Western diet, compared with the same mice on a chow diet (22). The increased SREBP-1c mRNA levels were associated with a significant increase in renal triglyceride levels.…”
supporting
confidence: 78%
“…This pathway directly regulates IL-8 transcription through binding to a novel gamma-interferon activation sequence (GAS) element in the IL-8 promoter. The sustained regulation of IL-8 transcription was found to be mediated by cholesterol depletion and the activation of the uncoupled eNOS/SREBP pathway 28,29 , which is sustained for up to 16 hours after Ox-PAPC treatment in HAEC. Increased binding of SREBP to an SRE element in the IL-8 promoter was also demonstrated.…”
Section: Chemokine Expressionmentioning
confidence: 96%
“…Oxidized phospholipids have been identified as potent mediators of inflammation (8,9). Berliner and colleagues have reported that oxidized phospholipids induce cytokine production in endothelial cells through induction of SREBP (10) via an endothelial nitric oxide synthase (eNOS)-mediated mechanism (11).…”
Section: /2mentioning
confidence: 99%